KAJIAN PERWUJUDAN NIRMANA INTERIOR GEREJA KATOLIK SANTO PAULUS DI SURABAYA DENGAN PENDEKATAN SEMIOTIK - Sari, Sriti Mayang; Fransisca, Sandy Ardina (Institute of Research and Community Outreach - Petra Christian University, 2008)
The physical interior of the St Paulus Catholic Church could be seen as a representation of core values in the Catholic's Liturgy. Thus every aspect and detail of the design must compromise with the true meanings of the liturgy with no exceptions from the perception of architect’s as well as the priest’s point of view. Furthermore the semiotic approach will produce the true meaning of core values in the Catholic Liturgy by looking through the signs and sysmbols that can be observed from each physical aspect of the interior of the church The expected result of the approach is the connotation and denotation value, which will be observed based on the design basics. Although the shapes and forms of the interior seem different from common catholic churches, it is observed that the St. Paulus Catholic Chucrh liturgy apparatus such as the altar, the pastor stand, the cross, as well as the room layout, etc still reflect representations of the core liturgy values in semiotic ways. Abstract in Bahasa Indonesia: Wujud fisik interior Gereja Katolik Santo Paulus Surabaya merupakan salah satu wujud dari nilai-nilai Liturgi Katolik. Oleh karena itu setiap unsur seharusnya disesuaikan dengan makna liturgi, walaupun dengan persepsi-persepi yang berbeda baik dari pihak arsitek maupun pastor paroki. Lebih lanjut, perwujudan nilai-nilai liturgi tersebut menjadi ‘tanda’ yang akan didekati secara semiotik sehingga ditemukan makna denotatif dan konotatifnya, yang ditinjau berdasarkan perwujudan nirmana. Secara semiotik perwujudan interior, seperti perwujudan bentuk lay out, elemen pembentuk ruang, dan perlengkapan liturgi di Gereja Katolik Santo Paulus Surabaya ini ternyata masih sesuai dengan nilai-nilai liturgi walaupun memiliki bentuk yang berbeda. Kata kunci: Interior Gereja Katolik, Pendekatan Semiotik.